2006
DOI: 10.1021/jp060955p
|View full text |Cite
|
Sign up to set email alerts
|

Local Density Inhomogeneities and Dynamics in Supercritical Water:  A Molecular Dynamics Simulation Approach

Abstract: Molecular dynamics atomistic simulations in the canonical ensemble (NVT-MD) have been used to investigate the "Local Density Inhomogeneities and their Dynamics" in pure supercritical water. The simulations were carried out along a near-critical isotherm (Tr = T/Tc = 1.03) and for a wide range of densities below and above the critical one (0.2 rho(c) - 2.0 rho(c)). The results obtained reveal the existence of significant local density augmentation effects, which are found to be sufficiently larger in comparison… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
54
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 52 publications
7
54
0
1
Order By: Relevance
“…Song and Maroncelli 62 systematically examined the disagreement between their simulation and experiment in the case of supercritical fluoroform. In that paper Song and Maroncelli pointed out that a possible reason for this discrepancy could be the assumption of a linear proportionality between spectral shifts and local densities as well as the methodology employed to derive local densities from the Raman shifts observed by Saitow et al 67 In general, several recent studies have provided information about the density dependence of spectroscopic observables 24,33,34,62,[71][72][73] in supercritical fluids. From these studies we may see that, in general, there is a nonlinear bulk density dependence; however the relation between these spectroscopic observables with the local density is still not very clear.…”
Section: -5mentioning
confidence: 99%
See 2 more Smart Citations
“…Song and Maroncelli 62 systematically examined the disagreement between their simulation and experiment in the case of supercritical fluoroform. In that paper Song and Maroncelli pointed out that a possible reason for this discrepancy could be the assumption of a linear proportionality between spectral shifts and local densities as well as the methodology employed to derive local densities from the Raman shifts observed by Saitow et al 67 In general, several recent studies have provided information about the density dependence of spectroscopic observables 24,33,34,62,[71][72][73] in supercritical fluids. From these studies we may see that, in general, there is a nonlinear bulk density dependence; however the relation between these spectroscopic observables with the local density is still not very clear.…”
Section: -5mentioning
confidence: 99%
“…The use of effective local densities to investigate local density inhomogeneities in supercritical fluids has been extensively discussed and justified in previous publications. 33,34,61,62 To calculate the effective local densities in SCW, we initially calculated the average coordination number N c corresponding to the first solvation shell of SCW at each state point,…”
Section: -5mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have already shown the ability of employed SPC (water) and OPLS (methanol) models to describe correctly the structure and thermodynamics of these liquids under supercritical conditions. 38,42,77 In order to compare the dynamics in water and methanol, simulations were performed at temperatures of T H 2 O = 775 K and T MeOH = 650 K. For both liquids, these temperatures are about 120 K and 140 K higher than their critical temperatures, respectively. To match the fast experimental laser heating of the liquids a rectangular box of each liquid at normal densities were heated to the respective temperatures (T H 2 O = 775 K; T MeOH = 650 K), neglecting molecules possibly present in the vapor phase during the heating in the experiment (due to the dimensions of the simulation box only a few of them would be present at the liquid-vapor interface).…”
Section: Resultsmentioning
confidence: 99%
“…[71] As equential molecular dynamics (MD) andq uantum mechanics approach was used by Millot et al to compute the UV/Vis spectrum of organic dyes, [72] and more recently Born-Oppenheimer MD simulations were performed by Canuto's group to study the electronic spectrum of para-nitroaniline. [73,74] The organization of the solvent around the solute and its influence on the solution structural and dynamic properties were investigated by means of MD for small solutes, [75][76][77][78][79][80][81][82][83][84] polymers [85,86] and proteins, [87] and passivated gold nanoparticles. [88] Some work based on Car-Parrinello MD was also performed.…”
Section: Computational Studies Of Solvation In Pure Sccomentioning
confidence: 99%